Ontology Based Integration of BIM and GIS for the Representation of Architectural, Structural and Functional Elements of Buildings - Korkmaz, Ozlem; Basaraner, Melih (COPERNICUS GESELLSCHAFT MBH, 2024)
Building Information Modelling (BIM) and Geographic Information System (GIS) integration allows for analysis and visualization of geospatial characteristics and relationships of buildings and their surroundings for in a number of domains such as planning and management of built environments and disaster management. BIM provides detailed geometric and semantic data about a building and its elements. Moreover, it is a technology that enables 3D display of architectural, structural, and mechanical, electrical, and plumbing (MEP) projects in a local cartesian coordinate system. On the other hand, GIS employs global (geographic or projected) coordinate systems, thereby allowing for the integration, analysis, and visualization of various geospatial data. The development of BIM and GIS for different purposes brings about differences in spatial focus, geometric and semantic representations, level of detail, coordinate systems, and other aspects. In order to eliminate these differences and ensure integration, geometric transformation and semantic transfer are required. The semantic web represents a logical preference for semantic transfer, characterised by a natural ability to integrate information from disparate sources. In this study, the detailed geometric and semantic data of a building with structural, architectural, and MEP projects in BIM were integrated with the geospatial data in GIS using a semantic web approach. For this purpose, an ontology including concepts, relationships, and attributes was developed with the contribution of core ontologies from BIM and GIS. Semantic and geometric data values related to the building and its elements were transferred to this developed ontology, which was formatted in RDF format. Queries were made using SPARQL to analyse the transferred data. The results of these queries indicated that the semantic web is well suited for use in BIM and GIS integration.
Keywords: Building Information Modelling; Geographic Information System; Data Integration; Semantic Transfer; Semantic Web; Computer Science; Remote Sensing